Simple Fabrication of Photodetectors Based on MoS2 Nanoflakes and Ag Nanoparticles - Xiao, Peng; Kim, Ju Hyung; Seo, Soonmin (Sensors, 2022)
Low-dimensional transition-metal dichalcogenides (TMDs) have recently emerged as promising materials for electronics and optoelectronics. In particular, photodetectors based on mono-and multilayered molybdenum disulfide (MoS2) have received much attention owing to their outstanding properties, such as high sensitivity and responsivity. In this study, photodetectors based on dispersed MoS2 nanoflakes (NFs) are demonstrated. MoS2 NFs interact with Ag nanoparticles (NPs) via low-temperature annealing, which plays a crucial role in determining device characteristics such as good sensitivity and short response time. The fabricated devices exhibited a rapid response and recovery, good photo-responsivity, and a high on-to-off photocurrent ratio under visible light illumination with an intensity lower than 0.5 mW/cm2.
Keywords: Dichalcogenides; Light sensor; Low dimensional; MoS2 nanoflake; MoS2 photodetector; Nano-flakes; Simple++; Transition-metal dichalcogenides; Visible light; Visible light sensor; MoS2 nanoflakes; MoS2 photodetectors; transition-metal dichalcogenides (TMDs); visible light sensor